Physico-chemical and Biological Variables of Hospitals Wastewater in Erbil City - Aziz, Rana; Al-Zubaidy, Fawzi; Al-Mathkhury, Harith; Musenga, John (Iraqi Journal of Science, 2023)
Three hospitals were chosen(Maternity hospital, Raperin hospital and Rhizgari hospital) for the present survey within Erbil city. Water samples were collected at regular monthly interval periods beginning in January 2012 to December 2012. pH of all the studied sites were found to be up 7. Electrical conductivity ranged from (1318-1790 μs.cm-1 in Maternity Hospital, 1770-2232 μs.cm-1 in Raperin Hospital, 1010-1615 μs.cm-1 in Rhizgari Hospital). BOD5 and COD values ranged from 22- 80 mg.L1 and 280- 1410 mg.L-1 respectively, this indicated a high pollution situation in the studied sites in respect to organic matter content. The quantitative analysis of counted microorganisms was more than that describe by WHO guidelines standard.